Corporate Social Responsibility and Governance: Information Disclosure in Multinational Corporations - Kaymak, Turhan; Bektas, Eralp (Wiley, 2017)
Multinational corporations (MNCs) are facing increasing pressure on two fronts - the demand for more transparency and disclosure and the need to implement good corporate governance practices. This paper develops several testable hypotheses that address these issues based on agency theory and stakeholder management approach arguments. As such, the relationship between corporate social responsibility (CSR) programs and firm-level governance structures are discussed. CSR is measured using Transparency International's study on the disclosure practices of the world's largest MNCs. Links between board size, board independence, and duality are explored. The results indicate that board independence and board size are strongly and positively related to several CSR practices. In addition, extractive industries have a significant and positive impact on the level of CSR activities. Policy and managerial implications related to these findings are also discussed. Copyright (c) 2017 John Wiley & Sons, Ltd and ERP Environment
Keywords: governance; corporate social responsibility; board structure; stakeholder engagement; disclosure; MNCs